Anxiety, pain, and nausea during the treatment of standard‐risk childhood acute lymphoblastic leukemia: A prospective, longitudinal study from the Children's Oncology Group. Issue 7 (15th January 2016) - Dupuis, L. Lee; Lu, Xiaomin; Mitchell, Hannah‐Rose; Sung, Lillian; Devidas, Meenakshi; Mattano, Leonard A.; Carroll, William L.; Winick, Naomi; Hunger, Stephen P.; Maloney, Kelly W.; Kadan‐Lottick, Nina S.
Abstract : BACKGROUND: This prospective study describes the procedure‐related anxiety, treatment‐related anxiety, pain, and nausea experienced by children with standard‐risk acute lymphoblastic leukemia (ALL) during the first year of treatment. METHODS: This study was undertaken at 31 Children's Oncology Group (COG) sites. Eligible children who were 2 to 9.99 years old were enrolled in a COG trial for patients with newly diagnosed standard‐risk ALL from 2005 to 2009. Parents completed a demographic survey at the baseline and the Pediatric Quality of Life Inventory 3.0 Cancer Module (proxy version) and the General Functioning Scale of the Family Assessment Device 1, 6, and 12 months after the diagnosis. The association between patient‐related (age, sex, ethnicity, and treatment), parent‐related (marital status and education), and family‐related factors (functioning, income, and size) and symptom scores was evaluated. RESULTS: The mean scores for procedure‐related anxiety, treatment‐related anxiety, and pain improved during the first year of treatment ( P < .0389). The mean nausea score was poorer 6 months after the diagnosis in comparison with the other assessments ( P = .0085). A younger age at diagnosis was associated with significantly worse procedure‐related anxiety ( P = .004). An older age ( P = .0002) and assignment to the intensified consolidation study arm ( P = .02) were associated with significantly worse nausea. CONCLUSIONS: Children with ALL experienced decreasing treatment‐related anxiety, procedure‐related anxiety, and pain during the first year of treatment. In comparison with scores at 1 and 12 months, nausea was worse 6 months after the diagnosis. Minimization of procedure‐related anxiety in younger children and improved nausea control in older children and those receiving more intensified treatment should be prioritized. Cancer 2016;122:1116–1125. © 2016 American Cancer Society Abstract : Children with acute lymphoblastic leukemia experience decreasing treatment‐related anxiety, procedure‐related anxiety, and pain over the first year of treatment. Nausea is worse 6 months after the diagnosis in comparison with 1 and 12 months after the diagnosis.